2003
DOI: 10.1128/mcb.23.7.2425-2437.2003
|View full text |Cite
|
Sign up to set email alerts
|

Myocardin Is a Critical Serum Response Factor Cofactor in the Transcriptional Program Regulating Smooth Muscle Cell Differentiation

Abstract: The SAP family transcription factor myocardin functionally synergizes with serum response factor (SRF) and plays an important role in cardiac development. To determine the function of myocardin in the smooth muscle cell (SMC) lineage, we mapped the pattern of myocardin gene expression and examined the molecular mechanisms underlying transcriptional activity of myocardin in SMCs and embryonic stem (ES) cells. The human and murine myocardin genes were expressed in vascular and visceral SMCs at levels equivalent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
290
1
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 330 publications
(308 citation statements)
references
References 53 publications
14
290
1
3
Order By: Relevance
“…In Xenopus animal cap cells, myocardin initiates the transcription of several SM markers, including SM22␣, SM ␣-actin, and calponin (Du et al, 2003;Small et al, 2005). We have confirmed those findings and extended it to SM-MHC.…”
Section: Transcription Factormediated Smooth Muscle Gene Expression Isupporting
confidence: 80%
See 1 more Smart Citation
“…In Xenopus animal cap cells, myocardin initiates the transcription of several SM markers, including SM22␣, SM ␣-actin, and calponin (Du et al, 2003;Small et al, 2005). We have confirmed those findings and extended it to SM-MHC.…”
Section: Transcription Factormediated Smooth Muscle Gene Expression Isupporting
confidence: 80%
“…A growing number of proteins, including GATA, MEF2, Nkx2.5 and myocardin family members have been shown to interact with SRF and modulate the transcription of target genes in a smooth muscle context (Miano, 2003). Myocardin and the myocardin-related transcription factors (MRTFs) are of particular interest because gain-and loss-of-function experiments showed that they were essential for the development and differentiation of SMC (Du et al, 2003;Li et al, 2003Li et al, , 2005Wang and Olson, 2004;Oh et al, 2005). The basic helix-loop-helix (bHLH) HAND proteins have also been implicated in the regulation of smooth muscle gene expression in mammals (Yamagishi et al, 2000;Morikawa and Cserjesi, 2004).…”
Section: Induction Of Smooth Muscle Gene Expression By Transcription mentioning
confidence: 99%
“…Prior studies indicate that smooth muscle development is controlled by a complex series of genetic and epigenetic events centered on the dynamic interactions between SRF and myocardin (Chen et al, 2002;Du et al, 2003;Kumar and Owens, 2003;Miano, 2003;Wang et al, 2003;Yoshida et al, 2003;McDonald et al, 2006;Pipes et al, 2006). The most striking feature of our expression profiling analysis is the observed down-regulation of SRF, myocardin, and 22 potential downstream target genes.…”
Section: Discussionmentioning
confidence: 78%
“…Genetic studies indicate the homeobox genes play an important role in determining the global patterning of the urogenital system (Satokata et al, 1995;Sciavolino et al, 1997;Warot et al, 1997;Goodman and Scambler, 2001;de Santa and Roberts, 2002;Troy et al, 2003), while key signaling molecules like sonic hedgehog and wnts have been implicated in determining the regional patterning within specific urogenital organs (Perriton et al, 2002;Freestone et al, 2003;Mericskay et al, 2004). The differentiation program responsible for the development of smooth muscle involves the complex interaction of epigenetic and genetic events including chromatin remodeling and acetylation, the SRF-myocar-din pathway, basic helix-loop-helix factors, AP-1 complex genes, and the ternary complex factors of the ETS domain family (Manabe and Owens, 2001;Chen et al, 2002;Du et al, 2003;Kumar and Owens, 2003;Miano, 2003;Wang et al, 2003Wang et al, , 2004Yoshida et al, 2003;Buchwalter et al, 2004;Spin et al, 2004;McDonald et al, 2006;Pipes et al, 2006). In addition, a variety of growth factors and hormones have been implicated in modulating the cell-to-cell interactions important for normal bladder morphogenesis (Cunha et al, 1980;Cerro et al, 1993;Finch et al, 1995;Krongrad et al, 1995;Mizuno et al, 1996;Haughney et al, 1998;Warner et al, 1999;Ince et al, 2002;Miyazaki et al, 2003;Villalpando and LopezOlmos, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Using siRNA approaches, studies from the Owens' laboratory suggest that KLF4 mediates, at least in part, the repressive effects of PDGFbb on SMC gene expression. This effect may occur as a consequence of KLF4 mediated repression of myocardin -a critical transcriptional coactivator involved in SMC differentiation [85,[87][88][89][90]. In contrast to PDGF-bb, TGFβ1 is known to induce SMC gene expression.…”
Section: Klf4mentioning
confidence: 99%